Being vulnerable with viewers: Exploring how medical YouTubers communicated about COVID-19 with the public. - Seung Woo Chae; Noriko Hara; Harshit Rakesh Shiroiya; Janice Chen; Ellen Ogihara (PLoS ONE)
This study explores COVID-19 communication between medical experts who upload YouTube videos related to health/medicine (hereinafter medical YouTubers) and their viewers. We investigated three specific elements: (1) how medical YouTubers' use of words related to analytical thinking is associated with their viewers' engagement, (2) how medical YouTubers' use of different types of emotion is associated with their viewers' engagement, and (3) the emotional alignment between medical YouTubers and their viewers. We collected 194 COVID-related video transcripts from five YouTube channels and 375,284 comments from those videos. We employed natural language processing to analyze the linguistic and emotional dimensions of these two text sets including analytical thinking, positive emotion, and negative emotion, the last of which was divided into anxiety, anger, and sadness. Additionally, three metrics provided by YouTube-the number of views, likes, and comments-were used as proxies representing user engagement. Our regression analysis results displayed that the medical YouTubers' analytical thinking was positively associated with the number of views. Regarding emotion, anxiety was positively correlated with the number of likes and comments, while both positive emotion and anger were negatively associated with the number of views. Finally, both positive and negative emotions of medical YouTubers were found to be positively correlated with the corresponding emotions of their viewers. Theoretical and practical implications of these findings are discussed within the context of COVID-19.